Peningkatan Pengetahuan Strategi Marketing Pada UMKM: (Studi Empiris Pada Angkringan Pak Yuli dan Soto Ayam Kampung Pak Pono) - Aninda Ira Mustikawati; Martinus Budiantara (Ebisnis Manajemen, 2024)
Humans are social creatures whose lives need clothing, food, and shelter. Everyone must have business opportunities and every business can be interpreted as a human effort to do something to achieve certain goals. Establishing a large, medium, small, or micro business is intended so that the business can have opportunities to develop and to maintain business and personal development. In a business, there must be conditions where competitive competitors can make it difficult for a business to achieve the expected profit. The amount of profit earned can be determined from the number of sales. This potential can be maximized with a marketing strategy by utilizing digital technology. Therefore, this community service activity is one of the efforts to build awareness of UKM business people regarding strategies that can be carried out to survive by utilizing social media and digital marketing in doing business.